Soil physicohydric properties and chisel energy demand in a compacted Alfisol - Mentges, Marcelo Ivan (2011)
The objective of this work was to evaluate the soil compaction effect on its physicohydric properties and on chisel energy demand, as well as to quantify the behavior of these properties below the chisel working depth. The experiment was carried out in a sandy loam Alfisol, with the following treatments: no-tillage for 13 years; no-tillage for 13 years and chiseling; no-tillage with additional compaction; and no-tillage with additional compaction and chiseling. Compaction along the chiseling depth was verified through data of traction effort associated to the chisel, obtained with the aid of an octagonal ring linked to a data acquisition module. Soil bulk density, total porosity, macroporosity, microporosity, hydraulic conductivity and soil resistance to mechanical penetration were also determined. Soil compaction increased both soil bulk density and resistance to mechanical penetration, reducing the total porosity and the macroporosity, without causing significant effects in microporosity. The compaction increased chisel energy demand in 21.64%, increasing the mean value of traction effort from 5.33 kN to 6.35 kN. Soil chiseling did not increase soil compaction status below the chisel working depth in the sandy loam Alfisol.